Manoyl oxide diterpenoids from Grindelia scorzonerifolia - Ybarra, María Inés (2005)
Two new norditerpenoids, 4β-hydroxy-19-normanoyl oxide (1) and 4α-hydroxy-18-normanoyl oxide (2), the new 18-O-α-L- arabinopyranosylmanoyl oxide (3a), and the known diterpenoids jhanol (4) and 18-hydroxy-13-epi-manoyl oxide (5) were isolated, together with other common plant constituents from an Argentine collection of Grindelia scorzonerifolia. The structures of the new compounds were established by extensive 1D and 2D NMR techniques and chemical transformations. Structural features of compounds 2 and 4 were verified by X-ray crystallographic analyses. The insecticidal effect of compound 3a was evaluated against the polyphagous pest Spodoptera frugiperda. Pupal and adult malformations leading to death occurred when 3a was incorporated in a larval diet at a concentration of 100 ppm. © 2005 American Chemical Society and American Society of Pharmacognosy.